Skema Saluran Pemasaran Pisang Mas Kirana: Kendala Utama dan Solusi Strategis - Rohmandani, Ade Yoga; Nisa, Khoirotun; Hermawan, Fariz Yudha (Program Studi Agribisnis, 2025)
Bananas are a commodity that continues to experience growth in East Java Province, one of the regions with diverse germplasm in the form of bananas is Lumajang Regency. The marketing aspect is a very important aspect, if the marketing mechanism runs well then all parties involved will benefit. The marketing channel functions as a distributor of producers to consumers, while a good and efficient marketing channel is a marketing channel that has the lowest marketing margin. Mas Kirana bananas have advantages that have been recognized by the government by obtaining a Global GAP (Good Agriculture Practice) certificate from the Dutch Control Union institution in March 2013. This is a special concern so that a marketing channel approach is needed by optimizing added value. This study uses the Systematic Literature Review (SLR) technique. There are four marketing channels for Mas Kirana bananas in Lumajang Regency, consisting of traditional marketing channels, modern marketing channels, e-commerce marketing channels, and export marketing channels. The shortest marketing channel is the e-commerce marketing channel which is the most efficient channel of the three other channels.